Microhabitat Distribution of Pseudodactylogyrus anguillae (Monogenea), Ergasilus gibbus and Ergasilus lizae (Copepoda) on the Gills of European Eels (Anguilla anguilla, L.) - (:unkn) unknown (INST ZOOLOGY, BAS, 2013)
Microhabitat distribution of Pseudodactylogyrus anguillae (Yin & Sproston, 1948) Gussev, 1965 (Monogenea: Dactylogyridae), Ergasilus gibbus von Nordman, 1832 and Ergasilus lizae Kroyer, 1863 (Copepoda: Ergasilidae) was studied on the gills of European eel Anguilla anguilla from Lake Koycegiz-Dalyan, Estuarine Channel System, Turkey. A total of 69 A. anguilla were examined between December 2009 and March 2010. A total of 1421 P anguillae, 143 E. gibbus and 63 E. lizae specimens were collected from the fish host. A prevalence of 81.15% and mean infection intensity of 25.16 for P anguillae, 50.72%, 4.0 for E. gibbus and 27.53%, 3.31 for E. lizae were found. Gill arches II, III, IV were preferred by P anguillae, gill arches I, II, III by E. gibbus and gill arches III, IV by E. lizae. In general occurrence of the parasite species, P anguillae preferred proximal-dorsal segments, E. gibbus distal-dorsal segments, whereas E. lizae exhibited a rather homogenous distribution. Site of attachment was the inner surface of the gill arches for E. gibbus and the outer surface for E. lizae. P. anguillae was found mostly on the inner surface of the hemibranches. Bispecific infections of P. anguillae with E. gibbus and E. lizae were also analysed individually. Finally, single species infections of the three parasite species were analysed.
Keywords: gill parasite; microhabitat; Monogenea; Copepoda; fish host; ectoparasites; MULLET MUGIL-CEPHALUS; MICRO-ECOLOGY; PARASITES; DACTYLOGYRUS; COEXISTENCE; ROSTRATA; TURKEY; FISHES; BINI